Antimicrobial Activity of the Essential Oil of Thyme and of Thymol against Escherichia coli Strains - Deise Flores Santurio (Acta Scientiae Veterinariae, 2014)
Background: The deterioration of food products, especially of those derived from meat, by pathogenic microorganisms is a major problem in industries. Escherichia coli is a facultative anaerobic bacteria of intestinal origin, and is a cause of concern in the meat industry. The use of essential oils as inhibitors of growth of spoilage and pathogenic microorganisms is a good choice for replacement of chemical additives in foods. This study was aimed at evaluating the in vitro activity of the essential oil of thyme (Thymus vulgaris) and thymol, against E. coli strains, by using a microdilution methodology based on the M31-A3 technique. Materials, Methods & Results: In this study the antimicrobial activities of the essential oil of Thymus vulgaris (thyme) and of the thymol compound were evaluated against 20 E. coli strains obtained from poultry and pigs. The strains are part of the collection of bacteria of the Laboratório de Pesquisas Micológicas of the Universidade Federal de Santa Maria (UFSM). The essential oil of thyme and its constituent, thymol, were commercially acquired (Sigma-Aldrich). Gas chromatography mass spectrometry (GC/MS) was realized on a Agilent chromatograph Model HP 6890 series CG, equipped with a mass selective detector 5973 with electron impact (CG-MS-EI) and identified p-cymene (23.71%), thymol (13.86%) and γ-terpinene (8.55%) as the major substances present in the thyme essential oil. The essential oil constituents were identified by comparing their mass spectra with those from the National Institute of Standards and Technology. The minimum inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) were determined for each isolate by using the broth microdilution technique based on the M31-A3 protocol. The geometric means of the MICs and MBCs against E. coli strains were of 627.7 μg.mL-1 and 990.2 μg.mL-1 for the thyme essential oil and of 2786 μg.mL-1 and 2540 μg.mL-1 for the thymol. These results show that the essential oil of thyme is a potential antimicrobial, and deserves further studies to be safely used as a preservative in foods. Discussion: The use of condiments, accompanied the process of civilization of humankind, which assures very low or no toxicity. These essential oils contain major components with significant antimicrobial activity. In this context, therefore, targeted studies are relevant to determine which essential oils are more active. Nonetheless, the inexistence of an international standardized technique for the evaluation of essential oils and vegetable extracts allows the use of different protocols, hampering the comparison of the results. The M31-A3 protocol used in our experiment is the most recommended among the techniques found in the literature. In this study, the essential oil of T. vulgaris and its major compound thymol showed bacteriostatic and bactericidal activities against E. coli strains in vitro. Nonetheless, the activity of the essential oil was superior to the compound a